The Drivers of River Temperatures Below a Large Dam. Issue 5 (29th April 2020) - Daniels, Miles E.; Danner, Eric M.
Abstract: Temperature is a fundamental aspect of water quality in rivers, controlling the rate of many ecological processes. By disrupting the flow of water, large reservoirs and dams can fundamentally alter downstream temperature regimes by resetting the water temperature and flow boundary conditions at the dam release point. Therefore, it is critically important to understand how the volume and temperature of these releases interact with meteorological conditions to influence downstream temperature dynamics. In this study, we modeled temperature dynamics in a large regulated river (Sacramento River, CA, USA) to better understand how heat fluxes, and ultimately river temperatures, responded to different physical drivers connected to meteorology and the upstream boundary conditions established by dam operations. We used a quantitative process‐based model of river temperature (RAFT), combined with sensitivity analysis, to identify the dominant physical drivers of temperature in the Sacramento River, and explored how these drivers varied over space and time. The physical drivers that had the greatest influence on temperature dynamics were dam discharge temperature, air temperature, and solar radiation. The primary controlling factors were dam discharge temperature in the most upstream reaches and air temperature in the most downstream reaches. When isolating the effect of boundary conditions on downstream river temperature, we observed that temperatures closer to the dam under all but low flow conditions responded more to changes in dam discharge temperature than dam discharge volume. Understanding the spatial and temporal extents of drivers of heat flux and their relative importance is critical when managing for river temperature. Key Points: Dam discharge temperature, air temperature, and solar radiation were the primary drivers of river temperature River temperature drivers varied spatially; dam discharge temperature drove upstream reaches and air temperature drove downstream reaches Dam discharge temperature was often a larger driver of downstream river temperature compared to discharge volume